Genome-wide analysis of the U-box E3 ubiquitin ligase enzyme gene family in tomato - Bhaskar Sharma (Nature Portfolio, 2020)
Abstract E3 ubiquitin ligases are a central modifier of plant signaling pathways that act through targeting proteins to the degradation pathway. U-box E3 ubiquitin ligases are a distinct class of E3 ligases that utilize intramolecular interactions for its scaffold stabilization. U-box E3 ubiquitin ligases are prevalent in plants in comparison to animals. However, the evolutionary aspects, genetic organizations, and functional fate of the U-box E3 gene family in plant development, especially in tomato is not well understood. In the present study, we have performed in-silico genome-wide analysis of the U-box E3 ubiquitin ligase gene family in Solanum lycopersicum. We have identified 62 U-box genes with U-box/Ub Fusion Degradation 2 (UFD2) domain. The chromosomal localization, phylogenetic analysis, gene structure, motifs, gene duplication, syntenic regions, promoter, physicochemical properties, and ontology were investigated. The U-box gene family showed significant conservation of the U-box domain throughout the gene family. Duplicated genes discerned noticeable functional transitions among duplicated genes. The gene expression profiles of U-box E3 family members show involvement in abiotic and biotic stress signaling as well as hormonal pathways. We found remarkable participation of the U-box gene family in the vegetative and reproductive tissue development. It is predicted to be actively regulating flowering time and endosperm formation. Our study provides a comprehensive picture of distribution, structural features, promoter elements, evolutionary relationship, and gene expression of the U-box gene family in the tomato. We predict the crucial participation of the U-box gene family in tomato plant development and stress responses.